MEER AS NOG ‘N KLIP IN DIE BOS - Collings, Steven (PINS-Psychology in Society, 2025)
Richter, L, Dawes, A, & Craig-Smith, C (2004) Sexual abuse of young children in southern Africa. Cape Town: HSRC Press. ISBN 0 7969 2053 2. Pages 478. It is generally acknowledged that child abuse interventions need to be informed by an evidence-based approach to practice which requires more than a reliance on one or two studies to support interventions. Rather, what is required is a reliance on syntheses of available research findings in the context of other equally legitimate influences on decision-making. In this context, Sexual abuse of young children in Southern Africa represents a preliminary, and certainly timely, attempt to provide a locally relevant: “…resource for researchers, advocates, and service providers to better understand the phenomenon of child sexual abuse in the region and to translate this understanding into an integrated response.” (pxi)